A nationwide survey of urinary concentrations of neonicotinoid insecticides in China. (November 2019) - Zhang, Tao; Song, Shiming; Bai, Xueyuan; He, Yuan; Zhang, Bo; Gui, Mingwei; Kannan, Kurunthachalam; Lu, Shaoyou; Huang, Yanying; Sun, Hongwen
Abstract: Neonicotinoid insecticides (NEOs) are emerging pesticides of concern due to their potential toxicity to non-target species (e.g., bees, fish and birds). China is an important producer and user of NEOs in the world. Studies on human exposure to NEOs in China are very limited. In this study, urinary levels of six NEOs, namely acetamiprid (ACE), clothianidin (CLO), dinotefuran (DIN), imidacloprid (IMI), thiacloprid (THD), and thiamethoxam (THM) were determined in 324 individuals from 13 cities in China. Across all sampling locations, total NEO concentrations (ΣNEOs; sum of six NEOs) were dominated by CLO (median: 0.24 ng/mL), IMI (0.21 ng/mL), THM (0.15 ng/mL) and DIN (0.14 ng/mL) collectively accounting for 98% of the concentrations. Urinary concentrations of each NEO varied depending on the sampling location with the median values ranged from 0.057 to 1.2 ng/mL for CLO, from 0.036 to 0.83 ng/mL for DIN, from 0.069 to 3.2 ng/mL for IMI, and from 0.062 to 0.45 ng/mL for THM. Sex-related differences in IMI, ACE and ΣNEOs concentrations were observed with males presenting significantly higher urinary levels than did females. All six NEOs were significantly positively correlated ( r = 0.135 to 0.661, p < 0.05) with each other, suggesting that the exposure sources of NEOs are common or related. On the basis of urinary IMI levels, we calculated the median daily intake (DI; mean and range) of IMI to be 1.6 (4.1, <0.02–55) μg/day, or 0.034 (0.11, <0.0003–2.1) μg/kg bw/day. To our knowledge, this is the first study to document the ubiquitous occurrence of and human exposure to NEOs in China. Graphical abstract: Unlabelled Image Highlights: First nationwide survey of urinary NEOs concentrations in Chinese residents. Chinese residents are widely exposed to NEOs, regardless of sampling locations. IMI, THM, CLO, and DIN are the dominant NEOs. Males had significantly higher urinary levels of ΣNEOs than did females. Urinary NEOs levels are similar to those of urinary pyrethroid levels in China.